A promising negative electrode of asymmetric supercapacitor fabricated by incorporating copper-based metal-organic framework and reduced graphene oxide - Mohanadas, Dharshini; Mohd Abdah, Muhammad Amirul Aizat; Azman, Nur Hawa Nabilah; Abdullah, Jaafar; Sulaiman, Yusran (Elsevier, 2021)
A hybrid negative electrode was developed by combining a hydrothermally prepared copper-based metal-organic framework (Cu-MOF) and electrochemically synthesized reduced graphene oxide (rGO), which was labeled as MrGO. The MrGO composite was characterized using field emission scanning microscopy, Raman spectroscopy, Fourier transform infrared spectrometry and X-ray diffraction to confirm the presence of both Cu-MOF and rGO. Cyclic voltammetry, galvanostatic charge discharge and electrochemical impedance spectroscopy (EIS) were carried out to study the electrochemical properties of the MrGO negative electrode for asymmetric supercapacitor (ASC) application. The EIS analysis of the MrGO electrode revealed the lowest charge transfer resistance of 0.95 Ω compared to rGO (23.73 Ω) and Cu-MOF (10.23 Ω). The electrochemical measurements were performed on the MrGO electrode at a negative operating potential (−0.4 to 0 V) to emphasize the hybrid MrGO as a high-performance negative electrode. The novel ASC was then constructed utilizing the vanadium oxide/reduced graphene oxide (VrGO) as the positive electrode and the hybrid MrGO as the negative electrode. The VrGO//MrGO ASC device was successfully delivered a superior specific capacitance (483.9 F/g) and enormous specific energy (31.2 Wh/kg). The inclusion of incredibly conductive rGO in the MrGO electrode could synergistically enhance the cycling stability (92% over 4000 CV cycles) of the VrGO//MrGO ASC device.